Multi Pendekatan dalam Pendidikan Islam - Muhammad Rusdi Rasyid (LPPM IAIN Sorong, 2019)
This paper discusses Islamic education and approaches related to Islamic education. The phenomenon that exists in society is the lack of Islamic education even in an environment that Muslim is the majority as happened in Aimas, Sorong Regency. Therefore, it is necessary to develop Islamic education focusing on coaching, courses and advocacy. The proposed approach contains comprehension related to education comprehensively by experts in the field of Islamic education. It aims to understand clearly the meaning and root words of the term of education, so that in the explanation there is no longer any mistake for the meaning of the development of Islamic education. The development was applied in line with the educational theory proposed by Ki Hajar Dewantara, Ahmad Tafsir, and Law of the Republic of Indonesia Number 20 Tahuan 2003 concerning the National Education system Article 1 paragraph 10.